The diagnostic significance of blood-derived circRNAs in NSCLC: Systematic review and meta-analysis - Yu, Weijie; Liu, Ruixue; Miao, Zhoulin; Zhang, Liwei; Sheyhidin, Ilyar; Ainiwaer, Julaiti (Frontiers in Oncology, 2022)
Background:Circular RNA may be used as efficient tools for noninvasive fluid biopsy in diagnosing NSCLC .However, so far there is no relevant systemic meta-analysis to prove diagnosis value of NSCLC by using blood-derived circRNAs in clinical .Object to study is to clarify the relationship between circRNAs and diagnostic value through Meta-analysis . Method:A systematical search strategy was used to search relevant literatures in the databases of PubMed, Web of Science, Cochrane Library from 2017 to 2022. The relationship between circRNAs and the diagnostic accuracy of NSCLC was analyzed. QUADAS-2 was used as assessment tool to evaluate the quality of literature. STATA (version 17.0) software was applied to assess statistical analysis. Result:The meta-analysis includes 1093 patients with lung cancer and 959 controls.result are respectively the pooled Sensitivity 0.78（95%CI=0.71-0.83，I2=71.86)、the pooled specificity 0.76（95%CI=0.70-0.82，I2=70.12）、the pooled PLR 3.3（95%CI=2.6-4.2，I2=37.56）、the pooled NLR 0.29（95%CI=0.23-0.37,I2=64.67）、 DOR 11.42（95%CI=7.88-16.56，I2=99.05）、AUC0.84(95%CI=0.80-0.87).the subgroup analysis suggests that the NSCLC subgroup is the main reason of heterogeneity. Conclusion:In summory,circRNAs is a sort of valuable as diagnostic biomarkers for NSCLC in China.Further prospective studies about the diagnostic value of circRNAs should be performed in multiple countries.